Minimal influence of recrystallization on middle Miocene benthic foraminiferal stable isotope stratigraphy in the eastern equatorial Pacific. (16th January 2016) - Voigt, Janett; Hathorne, Ed C.; Frank, Martin; Holbourn, Ann
Abstract: Stable carbon and oxygen isotopes (δ 13 C and δ 18 O) of foraminiferal tests are amongst the most important tools in paleoceanography, but the extent to which recrystallization can alter the isotopic composition of the tests is not well known. Here we compare three middle Miocene (16–13 Ma) benthic foraminiferal stable isotope records from eastern equatorial Pacific sites with different diagenetic histories to investigate the effect of recrystallization. To test an extreme case, we analyzed stable isotope compositions of benthic foraminifera from Integrated Ocean Drilling Program Site U1336, for which the geochemistry of bulk carbonates and associated pore waters indicates continued diagenetic alteration in sediments > 14.7 Ma. Despite this diagenetic overprinting, the amplitudes and absolute values of the analyzed U1336 stable isotopes agree well with high‐resolution records from better preserved Sites U1337 and U1338 nearby. Our results suggest that although benthic foraminiferal tests of all three sites show some degree of textural changes due to recrystallization, they have retained their original stable isotope signatures. The good agreement of the benthic foraminiferal stable isotope records demonstrates that recrystallization occurred extremely rapidly (< 100 kyr) after deposition. This is confirmed by the preservation of orbital cyclicities in U1336 stable isotope data and δ 18 O values being different to inorganic calcite that would precipitate from U1336 pore waters during late recrystallization. The close similarity of the benthic foraminiferal stable isotope records between the sites allows the well‐resolved paleomagnetic results of Site U1336 to be transferred to Sites U1337 and U1338 improving the global geological timescale. Key Points: Benthic foraminiferal δ 13 C and δ 18 O preserved despite recrystallization of tests Orbital cycles preserved in isotope record indicate recrystallization in < 100 kyr Transfer of U1336 magnetostratigraphy to Sites U1337 and U1338 possible